Heat Transfer and Flow of Natural Convection Past a Semi-Infinite Vertical Plate - Helen Oyelami, Funmilayo; Emadifar, Homan; Sunday Fadugba, Emmanuel; Khademi, Masoumeh; A. Hamoud, Ahmed (Contemporary Mathematics, 2024)
This manuscript presents a numerical investigation of the flow of an electrically conducting, incompressible, viscous fluid past a heated vertical channel with thermal radiation influence. The study uses the Rosseland approximation to describe the radiative heat flux and employs Crank Nicolson's implicit finite difference method utilizing the MATLAB programming tool for solving the non-dimensional system of equations. The results demonstrate that an increase in the thermal radiation parameter leads to a decrease in both the velocity and temperature of the fluid. The main findings of the study highlight the impact of thermal radiation on natural convection and heat transfer processes. This research is significant as it contributes to the understanding of convective heat transfer phenomena and provides valuable insights for applications in science and technology.